PERANCANGAN DAN PEMBANGUNAN SISTEM INFORMASI MONITORING ORMAS PADA BADAN KESBANGPOL SUMATERA UTARA - Willy Andri Malau; Yahfizham Yahfizham; Raissa Amanda Putri (UIN Sumatera Utara Medan, 2022)
Community organization is a group formed by the community voluntarily based on the common aspirations, needs, and goals to be achieved. This community organization is not just built, but must have a clear permit. Many community organizations are formed in every region, not least in the province of North Sumatra. The agency that oversees all these organizations is the National and Political Unity Agency (BKBP) of North Sumatra Province. However, there is a current problem that is experienced, namely the absence of a forum that directly connects BKBP with existing community organizations, making it difficult for BKBP to monitor, know the location of the organization, and also make it difficult for the organization in terms of registering community organization permits because it still has to be done manually with bring all the files to the BKBP office. For this reason, this research will overcome these problems by utilizing technology through the development of a monitoring information system for community organizations, where this system can be used for registration of permits for community organizations, viewing activity reports, monitoring organizational activities, and reporting organizations that are troubling the community. This system is web-based using the PHP programming language and the Laravel framework.